His bundle pacing: a new strategy for physiological ventricular activation - Lewis,AJM; Foley,P; Whinnett,Z; Keene,D; Chandrasekaran,B (Journal of the American Heart Association : Cardiovascular and Cerebrovascular Disease, 2019)
The specialized fibers of the HisPurkinje system are essential for the maintenance of the coordinated, synchronous ventricular contraction via endocardial to epicardial and apical to basal electrical activation. The right ventricle has been the most commonly used site to deliver artificial pacemaker stimuli since the 1950s, although pacing from both right ventricular (RV) apical and septal positions causes ventricular dyssynchrony, which is in turn associated with deleterious consequences including impaired myocardial perfusion,1 mitral and tricuspid regurgitation,2 an increased risk of atrial fibrillation, and systolic contractile dysfunction.3 As a result, the risk of hospitalization for heart failure was strikingly increased in patients receiving a higher proportion of ventricular pacing in the DAVID (Dual Chamber and VVI Implantable Defibrillator) trial 4, 5 and MOST (Mode Selection Trial)6 alongside an increased risk of ventricular tachycardia/fibrillation.7 Current guidelines8 and pacemaker algorithms9 therefore promote the minimization of right ventricular pacing wherever possible; however, excessive restriction of RV pacing with, for example, long atrioventricular delays impairs atrioventricular synchrony, increasing the risk of atrioventricular block at higher atrial rates and predisposing to mitral regurgitation. Furthermore, current strategies for the reduction of RV pacing have not improved clinical outcomes.10